The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1371/journal.pone.0111433
|View full text |Cite
|
Sign up to set email alerts
|

Lights, Camera…Citizen Science: Assessing the Effectiveness of Smartphone-Based Video Training in Invasive Plant Identification

Abstract: The rapid growth and increasing popularity of smartphone technology is putting sophisticated data-collection tools in the hands of more and more citizens. This has exciting implications for the expanding field of citizen science. With smartphone-based applications (apps), it is now increasingly practical to remotely acquire high quality citizen-submitted data at a fraction of the cost of a traditional study. Yet, one impediment to citizen science projects is the question of how to train participants. The tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 12 publications
3
49
0
Order By: Relevance
“…With suitable resource allocation and a training protocol (e.g., Kitching et al 2005;Starr et al 2014), citizen involvement and environmental engagement can be fostered for short-and long-term projects (cf. Weaver 2013).…”
Section: Discussionmentioning
confidence: 99%
“…With suitable resource allocation and a training protocol (e.g., Kitching et al 2005;Starr et al 2014), citizen involvement and environmental engagement can be fostered for short-and long-term projects (cf. Weaver 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been observed that crowdsourcing can be improved by various means, including self-censoring of submissions when a user is uncertain of a response (Shah and Zhou, 2015), using videos rather than only text- or image-based instruction (Starr et al , 2014), having mini-breaks especially for complicated tasks (Rzeszotarski et al , 2013), presenting context-sensitive help (Andersen et al , 2012), and financial punishment for disagreement with other users (Shaw et al , 2011). Most research in crowdsourcing accuracy has been on paid workers, for example recruited through Amazon Turk.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been shown that the effectiveness of citizen monitoring declines rapidly when the taxonomical difficulty of a monitored group increases (Starr et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…; Starr et al. ). Such an approach provides an opportunity to collect large amounts of data from large areas and also allows the dispersal of organisms to be tracked.…”
Section: Introductionmentioning
confidence: 97%